Clinical Characteristics and Outcomes in Patients With Localized Gastric Langerhans Cell Histiocytosis: A Case Series - Tae-Se Kim; Soomin Ahn; Yang Won Min; Hyuk Lee; Jun Haeng Lee; Poong-Lyul Rhee; Jae J. Kim; Byung-Hoon Min (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Objectives Localized gastric Langerhans cell histiocytosis (LCH) characterized by abnormal proliferation of Langerhans cells in the stomach without systemic involvement, is rare; therefore, the clinical characteristics and outcomes of LCH remain unclear. We investigated the clinical characteristics and outcomes in patients diagnosed with localized gastric LCH and have also discussed treatment strategies for this rare disease. Methods The study included seven patients diagnosed with localized gastric LCH at our hospital between September 1997 and December 2023. We retrospectively reviewed medical records and analyzed the clinicopathological characteristics and patient outcomes. Results Endoscopically, localized gastric LCH appeared as a small erosion in the distal part of the stomach. Positron emission tomography-computed tomography revealed normal findings in 100.0% (4/4) of patients during pre-treatment workup. Immunohistochemical analysis using S-100 and CD1a showed immunopositive cells in all tested patients. Of the six patients who underwent follow-up, two (33.3%) showed metachronous recurrence at a location distinct from the initial site. However, all patients eventually showed spontaneous regression of the disease, and no gastric LCH-induced mortality was observed during follow-up. Conclusions Careful and regular surveillance may be sufficient for patients with localized gastric LCH without systemic involvement.